PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIFTIPE GROUP INVESTIGATION DALAM PENINGKATANHASIL BELAJAR IPS DI KELAS IV SDN 4 DAWUHAN SITUBONDO TAHUN AJARAN 2012/2013 - Gustilas Ade Setiawan (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2018)
The Useing of Cooperative Learning Models tipe Group Investigation in Improveing The Learning Result Social Studies in IV Grade State Elementary School 4 Dawuhan Situbondo. The purpose of this research was to describe of models cooperative learning model tipe group investigation in improving the process and learning result os social studies IV Grade State Elementary School 4 Dawuhan Situbondo. Thisresearch uses classroom action research techniques. The results showed that the use of cooperative learning model tipe group investigation, can improve the process and learning result Social studies in IV Grade State Elementary School 4 Dawuhan Situbondo. Selection of the appropriate method is an alternative that can be taken